A Rare Clinical Presentation of Cholangiocarcinoma - Elisa Gravito-Soares; Marta Gravito-Soares; Pedro Figueiredo; Luis Tomé (Case Reports in Gastrointestinal Medicine)
Cholangiocarcinoma is an uncommon tumor, often diagnosed in the context of obstructive jaundice. Brain metastasis rarely occurs with the cerebellum being a rare site of spread of this type of tumor. Few cases of cholangiocarcinoma have been reported in the literature and this type of tumor is associated with a very poor outcome. We present a very rare form of clinical presentation of cholangiocarcinoma with neurologic symptoms due to cerebellar metastases.